A Histologic Study of Imatinib Cardiotoxicity in Adult Male Rats - Al-Allaf, Luma; Alnuaeimy, Wahda (Open Access Macedonian Journal of Medical Sciences, 2023)
BACKGROUND: Cardiotoxicity is an unanticipated adverse effect associated with some chemotherapeutic agents. There are conflicting results about imatinib-induced cardiac toxicity. AIM: This study aims at investigating the possible cardiotoxic effects of imatinib in rat model through assessing the possible histopathological alterations that might develop. MATERIALS AND METHODS: This is a case–control and experimental study conducted over a period of 3 months at laboratory of postgraduate studies, Department of Anatomy, College of Medicine, University of Mosul, Mosul, Northern Iraq. Sixteen adult male Albino rats were randomly assigned to either “control group” or “imatinib-treated group.” The control group was gavaged with distilled water daily for 4 weeks while the second group was given oral imatinib (200 mg/kg/day) for the same duration. Animals were sacrificed by euthanization after 24 h of the last dose. Hearts were obtained and cardiac specimens were immersed in paraffin. Sections’ staining by hematoxylin (Harris)-eosin (H&E) and Massons’ Thrichrom. RESULTS: Rats treated with imatinib showed decreased physical activity and food intake. Regular arrangements of myofilaments were noticed during light microscopic examination of cardiac sections of control rats. However, sections from imatinib group showed several histological alterations (mainly myofibrillar loss in myocardium with vacuolated cytoplasm). Necrosis of cardiac muscle fibers was also noticed in some sections. Appearance of deeply staining cells with pyknotic nucleus, in addition to shrinkage of cardiac muscle fibers, was also noticed in some sections. The mean score of cardiac injury in the treated group was 2.1 (vs. 0.6 in controls). Some sections of treated group showed an increment (mild) in collagen fibers in-between cardiac myocytes. CONCLUSIONS: The observations concluded that imatinib has targeted action on cardiomyocytes. Oncologists should be cautious regarding imatinib dose and duration besides the close cardiac monitoring throughout and beyond therapy duration.